Statistical assessment of interrelationship of marriage and divorces to fertility - A. B. Sinelnikov; O. A. Zolotareva; M. D. Khabib (Вестник университета, 2025)
The methodology for analyzing interrelationship of marriage and divorces to fertility has been proposed, approbation of which has been carried out on the basis of the modern system of statistical accounting, which allowed to form a unique system of statistical indicators of marriage and divorce. A number of indicators complement the traditional methodology of marriage and divorce tables calculation. The algorithms for obtaining the indicators proposed for implementation (in particular, the cumulative marriage rate of divorcees, the level of divorces compensation by legal remarriages, etc.) have been prescribed, and their estimations have been made, which substantiates the scientific significance of the study. The methodology makes it possible to assess the impact of marriage and divorce rates on fertility, to identify the impact of measures of state assistance to families on the change in the number of marriages, divorces, and births, and also makes it possible to justify new measures of demographic policy aimed at increasing the marriage rate and reducing the divorce rate. The author’s approach considers the current trends in the analyzed demographic processes characteristic of Russia, which determines its predictive capabilities. It indicates high practical significance of the research results in the context of the search for fertility growth reserves in the light of the implemented family and demographic policy and achieving Russia’s national development strategies.